Topical Application of St. Johnʼs Wort (Hypericum perforatum) - Wölfle, Ute; Seelinger, Günter; Schempp, Christoph M. (Planta Medica, 2014)
St. Johnʼs wort (Hypericum perforatum) has been intensively investigated for its antidepressive activity, but dermatological applications also have a long tradition. Topical St. Johnʼs wort preparations such as oils or tinctures are used for the treatment of minor wounds and burns, sunburns, abrasions, bruises, contusions, ulcers, myalgia, and many others. Pharmacological research supports the use in these fields. Of the constituents, naphthodianthrones (e.g., hypericin) and phloroglucinols (e.g., hyperforin) have interesting pharmacological profiles, including antioxidant, anti-inflammatory, anticancer, and antimicrobial activities. In addition, hyperforin stimulates growth and differentiation of keratinocytes, and hypericin is a photosensitizer which can be used for selective treatment of nonmelanoma skin cancer. However, clinical research in this field is still scarce. Recently, sporadic trials have been conducted in wound healing, atopic dermatitis, psoriasis, and herpes simplex infections, partly with purified single constituents and modern dermatological formulations. St. Johnʼs wort also has a potential for use in medical skin care. Composition and stability of pharmaceutical formulations vary greatly depending on origin of the plant material, production method, lipophilicity of solvents, and storage conditions, and this must be regarded with respect to practical as well as scientific purposes.
Keywords: St. Johnʼs wort; Hypericum perforatum; Hypericaceae; topical application; dermatology